PERBANDINGAN TIKTOK SHOP DAN SHOPEE DARI PERSPEKTIF SELLER: PELUANG, TANTANGAN, DAN POTENSI INCOME - Nadhifa Zulfa Shafira Aziz; Zulfa Dina Mardhiyah; KhoirotulFadzillah; Siti Nur Aziza (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This qualitative study aims to analyze and compare TikTok Shop and Shopee from the perspective of online sellers in Indonesia, focusing on opportunities, challenges, and income potential. Data were collected through semi-structured interviews with four sellers active on both platforms. The findings indicate that Shopee offers operational convenience and a more stable income pattern due to its mature ecosystem, whereas TikTok Shop provides higher income potential during viral content or live-selling sessions, albeit with greater creative and algorithmic challenges. Promotional strategies, content engagement, and platform management systems are key determinants of seller success. The study concludes that both platforms are complementary in Indonesia’s digital commerce landscape, and sellers benefit from a hybrid strategy integrating Shopee’s stability with TikTok’s dynamic engagement.